“I don’t want to be a victim again”: the impact of repeat assault on police officers - Davidson, Louise; Dennis, Amelia; Theodoropoulou, Andriana; Carter, Holly; Amlôt, Richard; Hesketh, Ian (Frontiers in Psychology, 2023)
Introduction The frequency of assaults on police officers in the United Kingdom is rising and evidence suggests that exposure to work-place violence can negatively impact wellbeing, for example, increased perceived stress, feeling worn out and tired, and emotional exhaustion. Despite the prevalence of assaults on police officers, little research has examined the impact of repeat assaults on officers’ wellbeing. Method For the current study, 12 semi-structured interviews were conducted to investigate the impact of repeat assaults on wellbeing and occupational outcomes in police officers and staff, including impacts on their mental and physical heath, impacts on their work, the impact of prior assaults on future assaults, and what support they were provided with. Results Findings indicate that repeat assaults had a negative impact on participants mental and physical wellbeing. Furthermore, a lack of support both from management and peers within the police force was found to further exacerbate the impact of repeat assaults. However, the provision of support was also identified as a mitigating factor when it was available and provided to participants which helped to protect participants from some of the negative impact of repeat assaults. Discussion Findings provide a unique in-depth perspective into police officers’ experiences following repeat assaults, which can in turn inform national policies and help tailor effective support services within the police force.